Pharmacological management of pediatric insomnia - Dhir, Sakshi; Karim, Nicolette; Berka, Haley; Shatkin, Jess (Frontiers in Sleep, 2024)
Insomnia is the most commonly reported sleep disorder among children and adolescents, impacting their cognitive, emotional, behavioral, and physical development. The prevalence of insomnia generally increases with age, often persisting into adulthood if unaddressed. Insomnia is exceedingly common among those with developmental disabilities and is frequently comorbid with a great range of psychiatric diagnoses. The COVID pandemic has only increased the prevalence of insomnia among children and adolescents. Health care providers are routinely called upon to treat insomnia in the pediatric population. Psychoeducation and behavioral interventions, especially cognitive behavioral therapy for insomnia (CBT-I), remain the first line treatments, given empirical evidence for their efficacy and success in relapse prevention. However, medications are frequently employed in clinical practice, despite the fact that no medications are approved by the Food and Drug Administration (FDA) for the treatment of pediatric insomnia. This review was designed to educate and support practitioners who are treating children and adolescents who struggle with insomnia. A thorough narrative review was completed to identify all published medication studies of pediatric insomnia; the identified studies are described and then graded into four categories according to the strength of the evidence supporting their use, side effect profiles, co-morbidities, and overall risk versus benefit of each pharmacological treatment. This review will help practitioners in making clinical decisions for their pediatric patients who suffer with insomnia.